Characterization of Water Quality and Evaluation of Pollution Levels Around Final Disposal Sites (TPA) - Ika Bagus Priyambada; Ariesta Sulistyo Asih; Winardi Dwi Nugraha; Muhammad Bintang Wahyuarta (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
This study evaluates water quality and pollution levels surrounding the Degayu Landfill, Pekalongan City, focusing on nutrient characteristics. Landfills generate leachate containing organic and inorganic compounds that can contaminate nearby water bodies if mismanaged. We conducted a survey by sampling water at several locations around the landfill to analyze nutrient-related parameters, specifically ammonia, nitrite, and phosphate. The data were analyzed descriptively, compared with applicable water quality standards, and assessed using the pollution index method to determine overall water quality status. Furthermore, Spearman correlation analysis identified relationships among these parameters. Results indicate varying nutrient concentrations, with increases at specific locations. The pollution index values suggest a decline in water quality at several observation points relative to established standards. Notably, correlation analysis revealed a strong relationship between ammonia and nitrite, highlighting their role in nitrogen transformation within the aquatic environment. In conclusion, water quality around the Degayu Landfill is demonstrably influenced by nutrient concentration variations, indicating a potential impact on the ecological balance of the surrounding aquatic ecosystem